UPAYA MENINGKATKAN KEMAMPUAN MENGENAL KOSA KATA PADA ANAK MELALUI PENDEKATAN MODEL EXPERIENTAL LEARNING - Ratu Yustika Rini (LPPM Universitas Bina Bangsa, 2022)
Vocabulary is an important element in the development of language skills in early childhood. The development of this vocabulary understanding skill requires a complete understanding to be obtained by the child. This research has the hope of being able to improve children's ability to recognize vocabulary in children by using the Experiential Learning Approach in group A of Ulil Albab Kindergarten. This research uses Classroom Action Research (CAR). The sample of this study involved 12 children in group A. The data collection process in this study was carried out by carrying out two cycles of action. The results of this research action have shown an increase in the child's ability to recognize vocabulary and indicate an increase that has been made in cycle one which shows a result of 61.1% where half of the sample has shown an increase, then in the second cycle the actions that have been taken show an increase again by 91.1%. The researcher concludes that the researcher's efforts in improving the ability to recognize vocabulary in children through an experiential learning model approach are well applied to Ulil Albab Kindergarten